Modelagem física de colunas granulares compactadas de RCC parcialmente reforçadas com geossintéticos - Albino, Jordan Lopes (Universidade Federal de São Carlos, 2019)
Granular Columns has been intensively used as soil improvement for spread footings, embankments and other applications. The filling material of columns is generally crushed stone or sand. However, replacing these natural materials for construction-recycled wastes would provide a sustainable uses for this this material without losing technical benefits provided by natural filling material. In soft soils, geosynthetics have been applied as encasement of granular columns improving lateral confinement and, consequently, the stiffness and bearing capacity. Most of studies in literature involving geosynthetic-encased columns are limited for improvement of soft soils, whereas limited are the applications in cohesive soils with low bearing capacity. Therefore, this study aims to evaluate the mechanical and geotechnical behavior of construction waste granular columns reinforced with geosynthetics used as ground improvement of shallow foundations in a low strength cohesive soil. In order to provide viability of this technique, it was evaluate the mechanical behavior of granular columns partially reinforced with geosynthetics as encasement and as internally layered reinforcements. The study was based on load plate tests of small-scale 1-g physical models constructed in laboratory (10:1). The simulated foundation soil used in this research was a sandy-clay material with relatively low shear strength and stiffness. The column length was 40 cm with pre-compacted diameter of 5.5 cm. The steel plate was 20 cm in diameter and 3 cm thickness. Four load plate tests were performed: (i) on the foundation soil; (ii) on the soil improved with unreinforced granular column; (iii) on layered reinforced geogrid granular column; (iv) on the partially encased column. For the layered reinforced column, geogrids were positioned spaced each 2.5 cm from the top of the column, comprising in four layers of reinforcements. In the case of the partially encased columns, the geotextile covered the length of 11 cm (2D) from the top of the column. The tests were instrumented with load cell, displacement transducers for settlement monitoring, and earth pressure cells positioned at the base and at the top of the column for assessment of load transference during tests. Results demonstrated that the use of granular columns with recycled wastes reduced vertical displacement and improved bearing capacity of soil. The use geogrid layered reinforcement columns led to a significant improvement on the stiffness of foundation soil, although not changing the bearing capacity. On the other hand, the use of the partially encasement columns was found to improve both bearing capacity and stiffness. The study demonstrate the viability of using of recycled construction waste columns as a soil reinforcement providing sustainable and technical benefits mainly when using geosynthetics reinforcements.
Keywords: Colunas granulares; Geogrelha; Resíduo de construção civil; Modelo físico; Granular columns; Geosynthetic; Construction and demolition waste; Physical modelling; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA